(untitled) (Quaderni di Gargnano, 2022)
This essay will trace the ideological circumstances surrounding the composition of two of Dante’s "minor works": the Vita nova and the Convivio. The inquiry into the inspiration of and the motives for the material projects of the two texts (based on information available to us today) will be followed by a study of their cultural significance in the later works and in the tradition as a whole. Il presente intervento si propone di tracciare i contorni delle circostanze ideologiche che hanno reso possibile la composizione delle due opere "minori" dantesche: la Vita nova e il Convivio. Dopo aver indagato l’ispirazione e i motivi del loro progetto materiale a partire dalle informazioni a nostra disposizione, si tratterà del loro significato culturale all’interno delle opere successive e di quelle della tradizione.